42.4k views
5 votes
Super genius people. here question mark

Super genius people. here question mark-example-1
User Nicojo
by
5.4k points

2 Answers

7 votes

Answer:

6√5 - 4√7

Explanation:

hope it helps!!

Super genius people. here question mark-example-1
User Samuel Thompson
by
4.5k points
0 votes


3 √(5) - 2 √(7) + √(9 * 5) - √(4 * 7) \\ = 3 √(5) - 2 √(7) + ( √(9) * √(5) ) - ( √(4) * √(7) ) \\ = 3 √(5) - 2 √(7) + 3 √(5) - 2 √(7) \\ = 3 √(5) + 3 √(5) - 2 √(7) - 2 √(7) \\ = 6 √(5) - 4 √(7)

OPTION C IS THE ANSWER.

User Christer
by
6.2k points